Case Report: Anti-NMDA Receptor Encephalitis With Bilateral Hearing Loss as the Initial Symptom - Cheng, Hongjiang; Yang, Fengbing; Zhang, Jing; Xu, Lina; Jia, Longbin; Zhao, Doudou; Liu, Wei; Li, Huimin (Frontiers in Neurology, 2021)
Introduction: Anti-N-methyl-D-aspartate receptor (anti-NMDAR) encephalitis is an autoimmune disease associated with the NMDA receptor. This paper describes a patient who presented with bilateral hearing loss as the initial symptom of anti-NMDAR encephalitis. Case Report: We describe a 31-year-old young female with anti-NMDAR encephalitis who presented with bilateral severe hearing loss after brief loss of consciousness and then accompanied by other symptoms, such as generalized tonic–clonic seizures, manic episodes, excessive salivation, severe cognitive impairment, and complex non-convulsive status epilepticus. Great improvement was achieved by a combined treatment of steroid, IVIG, and plasmapheresis, especially after surgical removal of the ovarian teratoma. When she was discharged on hospital day 43, her hearing loss obtained a significant improvement. Conclusion: This case study and literature review investigated the impairment of hearing loss and its subsequent treatment in patients with anti-NMDAR encephalitis.